Vad händer i hjärnan när vi blir rädda? - En visualisering - Lindquist,Adam; Brax,Alexander (2025)
In order for a person to experience a fear response, a platitude of different brain parts and processes are required. Both small parts, like the amygdala and hypothalamus, and larger parts, like the prefrontal cortex, are necessary. While a lot of fear responses have a similar outline, there are differences in the expressions and activations of the brain parts. In this project, a prototype model of a brain is built in order to showcase an explicit and implicit fear response in a simplified manner. Anxiety is also showcased alongside its differences to the other fears. The prototype, which is built of an arduino-circuit, led diodes, and other electrical components, is intended to be developed into a full-scale model at Vattenhallen Science center at Lund university. The intentions behind this model is to educate about the complex processes through the help of programming and the use of circuitry. The project is composed of three parts: the literature study, the programming of the arduino, and the design of the prototype. In the end, the model became a two dimensional illustration of the brain with lights being placed on the involved brain structures. The model also has a speaker illustrating the increase in heart rhythm while showcasing differences in fear responses through light activation.